A Systems and procedures study of United Coconut Planters Bank, Garnet Branch Savings Account Division - Botuyan, Jean; Pascual, Kathleen; Rivera, Ruby; Sy, Bernabeth (College of Engineering, 1991)
The group has undertaken a financial institution for this Systems and Procedures Study. Such study is a branch of United Coconut Planters Bank situated in Cainta. Among the numerous activities that the bank is engaged in the group has decided to narrow down the study to it's current Savings Account divisions. Basically the said activity entails the following transactions : Opening of Accounts, Regular Deposits Withdrawals Afternoon Transactions Replacement Closing of an Account and Cash Transfers (maybe from vault to window or vice versa). Under the activities mentioned the specific forms used together with their inspection, transposition and means on how each one are processed are discussed within the text which declares the state of the present system. Towards the end the group has consolidated all of the data that it was able to gather and has come up with alternative solutions and finally concrete recommendations on how each system can be improved. Generally the proposals made on the improvement of the division as a whole entails either a re-distribution of work load among the workers or an alteration in the work sequence of the specific transaction.